Hospitalizations and deaths from diabetes mellitus in northeastern Brazil between 2010 and 2019 - Luan Wesley Marques Máximo; Augusto Cezar Antunes de Araujo Filho; Hernandes Flanklin Carvalho Oliveira; João Victor de Sousa Lima; Thatiana Araújo Maranhão (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To identify the epidemiological profile of hospitalizations and deaths due to Diabetes Mellitus, based on secondary data, in the Northeastern Brazilian States, between 2010 and 2019. Methods: Ecological, time series study that used secondary data extracted from the website of the Department of Informatics of the Unified Health System (DATASUS). The population of this study consisted of all hospitalizations and deaths due to Diabetes Mellitus of people living in the Northeastern Brazilian States during the period investigated. The following variables were investigated: age group; sex; color/race; character of care due to hospitalization and deaths due to Diabetes Mellitus. Results: During the period there were fluctuations in the mortality rate, with a decreasing trend, but without statistical significance (p=0.0523). It was observed that older adults, women and browns are more frequent among hospitalizations. In addition, it was found that the older adults suffered more emergency hospitalizations compared to elective ones. There was a statistically significant association in the variables, age group, sex and race and type of care (p<0.001). Older adults, women and browns are the most prevalent among deaths, regardless of the nature of care. Conclusion: Deaths and hospitalizations due to Diabetes Mellitus were...